2009
DOI: 10.1016/j.yjmcc.2008.10.014
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial dysfunction in adiponectin deficiency and its mechanisms involved

Abstract: Endothelial dysfunction is the earliest pathologic alteration in diabetic vascular injury and plays a critical role in the development of atherosclerosis. Plasma levels of adiponectin (APN), a novel vasculoprotective adipocytokine, are significantly reduced in diabetic patients, but its relationship with endothelial dysfunction remains unclear. The present study aims to determine whether APN deficiency may cause endothelial dysfunction and to investigate the involved mechanisms. Vascular rings were made from t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

4
81
0
13

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 115 publications
(98 citation statements)
references
References 38 publications
4
81
0
13
Order By: Relevance
“…Proinflammatory cytokines impair endothelial function in animal models and in isolated human veins (3,10,33). Previous studies show that insulin resistance and T2D are associated with increased proinflammatory cytokines such as TNF-␣ and IL-6 as well as decreased plasma adiponectin (APN) (8,15,35,54). We hypothesize that exercise training (ET) improves endothelial function in the diabetic aorta by suppressing oxidative stress and inflammatory process thereby increasing NO bioavailability.…”
mentioning
confidence: 96%
See 3 more Smart Citations
“…Proinflammatory cytokines impair endothelial function in animal models and in isolated human veins (3,10,33). Previous studies show that insulin resistance and T2D are associated with increased proinflammatory cytokines such as TNF-␣ and IL-6 as well as decreased plasma adiponectin (APN) (8,15,35,54). We hypothesize that exercise training (ET) improves endothelial function in the diabetic aorta by suppressing oxidative stress and inflammatory process thereby increasing NO bioavailability.…”
mentioning
confidence: 96%
“…Thus endothelial dysfunction with inflammatory cell and platelet adhesion may contribute to the development of atherosclerosis in T2D. Even though the mechanisms responsible for endothelial dysfunction are not fully elucidated, previous studies indicate that a decrease in nitric oxide (NO) bioavailability may play a central role in endothelial dysfunction in T2D (32,36,54).In addition, oxidative stress and chronic inflammation are important pathogenic factors in many diseases including T2D and cardiovascular diseases (CVD) such as stroke, coronary artery disease, and atherosclerosis (8,19,28,32). Previous studies indicated that reactive oxygen species (ROS) such as superoxide (O 2 ·Ϫ ) readily react with NO to form peroxynitrate (ONOO Ϫ ), which results in decreased NO bioavailability (8,10,32,47).…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Insome studies a positive correlationof adiponectinwithretinopathy andalbuminuria in T1DM was found (29,30). In animal and cell culture studies adiponectin increased the bioavailability of NO directly, stimulating eNOS, and indirectly, by reducing the concentration of superoxide products (27)(28)(29). Sharma et al (2008) The results of recent experimental studies suggest an increased expression of DPP-4 in adipocytes of visceral fat and increased serum enzymes in patients with IR and T2DM (39,40).…”
Section: Evaluation Of the Hypothesismentioning
confidence: 99%